الاستراجيات والتحديات في سياسة برنامج تعليم اللغة العربية = Strategies and obstacles on educational policy of Arabic language program - Yaakub, Muhamadul Bakir (Kolej Islam Darul Ridzuan, Perak, 2012)
This paper highlighted general description of the ongoing Arabic Language Teaching Program (ALTP) in Malaysia. The critical issues addressed contain some determining factors involved within the educational policies applied and its operational strategies practised within the environmental constraints and sociocultural impacts. At the same time it is also an attempt to bring forward a brief discussion on the challenges confronted by Arabic language learners as a second language, whereby the focus of the case is based on the context of Malaysian educational setting.